Deproteinized Bovine Bone Mineral or Autologous Bone at Dehiscence Type Defects at Implants Installed Immediately into Extraction Sockets: An Experimental Study in Dogs - Pereira, Flavia Priscila [UNESP]; Santis, Enzo de; Vieira, Eduardo Hochuli [UNESP]; Souza Faco, Eduardo F. de[UNESP]; Pantani, Fabio; Salata, Luiz A.; Botticelli, Daniele (Wiley, 2015)
Purpose: The aim of this study was to evaluate bone regeneration at surgically created dehiscence buccal defects at implantsplaced immediately into extraction sockets (IPIES) of small dimensions filled with autogenous bone or deproteinizedbovine bone mineral (DBBM) associated with a collagen membrane.Materials and Methods: Eight Labrador dogs were used and implants were placed immediately into the extraction socketsof the second premolar. The buccal wall was subsequently removed to create a standardized defect, 4 mm wide coronally,2 mm wide apically, and 6 mm high. Autogenous bone particles (AB) or DBBM g ranules were used to fill the defects. Allsurgical sites were subsequently covered by a resorbable collagen membrane and a non-submerged healing was allowed.After 4 months, the animals were euthanized and bone blocks harvested and processed for histomorphometric analysis.Results: The bon y cr est at the buccal aspect (C) was located 2.3 1 0.8 mm and 1.7 1 0.7 mm apically to the implant shoulder (IS)at the AB and DBBM sites, respecti v ely. The cor onal lev els of osseointegration at the buccal aspect (B) we re locat ed 2.7 1 0.7 mmand 2.2 1 1.0 mm apically t o IS at the AB and DBBM sites, respecti v ely. A t the AB sites, the peri-implant muc osa was located4.3 1 0.9 mm, 4.7 1 0.9 mm, and 2.0 1 1.6 mm cor onally t o C, B, and IS, respecti vely. The corresponding values at the DBBM siteswer e 4.3 1 0.6 mm, 4.8 1 0.6 mm, and 2.5 1 0.8 mm, r espectiv ely. N o statistically significant differenc es wer e found.Conclusions: The treatment of surgically created buccal defects at IPIES sites using Bio-Oss® (Geistlich Biomaterials,Wolhusen, LU, Switzerland) or autogenous bone, concomitantly with a collagen membrane, engenders bone regenerationto a similar extent after 4 months of healing.
Keywords: DBBM; Animal study; Autologous bone; Bone healing; Collagen membrane; Extraction socket